(3CSGSjGJ GdeMGSHI h WQbgG (B/s - (3YHO Gddg, NGdO Gejfs; (3MeRI HTjQ, CHh YGUjs ((3YeGf(B: s (3OGQ hGFd(B, s, 2001)
(3eYdheGJ JegjOjI Mhd GdeMGSHI , GdfXGe GdeMGSHj h fXQjGJ GdbjO GdeMGSHj , eMGSHI GdeTQhY GdaQOj hab fXGe GdjhejI h YedjGJ gG GdeTQhY aj OaJQ GdjhejI h OajQ GdCSJGP , ejRGf GdeQGLYI h GdGNWGA , GdMSGHGJ GdNJGejI h GdejRGfjI GdYehejI , GdLQO h GdJShjGJ GdLQOjI , GdWQb GdeMGSHjI h GdMSGHGJ GdGLeGdjI(B.s
Keywords: (3GdeMGSHIs; (3GdejRGfjI GdYGeIs; (3JObjb GdMSGHGJs